2016
DOI: 10.1186/s12890-016-0332-z
|View full text |Cite
|
Sign up to set email alerts
|

Is there any association between Sarcoidosis and infectious agents?: a systematic review and meta-analysis

Abstract: BackgroundDuring the last few years, investigators have debated the role that infectious agents may have in sarcoidosis pathogenesis. With the emergence of new molecular biology techniques, several studies have been conducted; therefore, we performed a meta-analysis in order to better explain this possible association.MethodsThis review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement from the Cochrane collaboration guidelines. Four diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 74 publications
1
71
0
7
Order By: Relevance
“…A systematic review of 58 studies (> 6,000 patients) found a link between sarcoidosis and both P acnes, and mycobacteria. 63 Herpesvirus has also been implicated, although viruses have not been known to trigger granulomatous reactions. 64 Various other pathogens studied, including Borrelia, Rickettsia helvetica, Chlamydia pneumoniae, EBV, and retroviruses, were not associated with sarcoidosis.…”
Section: Other Idiopathic Interstitial Pneumoniasmentioning
confidence: 99%
“…A systematic review of 58 studies (> 6,000 patients) found a link between sarcoidosis and both P acnes, and mycobacteria. 63 Herpesvirus has also been implicated, although viruses have not been known to trigger granulomatous reactions. 64 Various other pathogens studied, including Borrelia, Rickettsia helvetica, Chlamydia pneumoniae, EBV, and retroviruses, were not associated with sarcoidosis.…”
Section: Other Idiopathic Interstitial Pneumoniasmentioning
confidence: 99%
“…This is the first study to identify mycobacteria from cutaneous sarcoidosis specimens using REBA. The molecular techniques used in previous reports to identify mycobacterial DNA from sarcoidosis lesions were primarily nested or real‐time PCR . However, REBA hybridizes the PCR products of the DNA extracted from specimens on to a fixed mycobacterial DNA template and thus exhibits increased sensitivity as it amplifies the PCR results .…”
Section: Discussionmentioning
confidence: 99%
“…Sarcoidosis is a differential diagnosis of tuberculosis (TB), and the two diseases are similar in clinical and histopathological presentation . Owing to their similarities, it has long been proposed that Mycobacterium tuberculosis (MTB) is one of the causative antigens of the inflammatory cascade that results in sarcoidosis . Furthermore, some researchers have suggested that sarcoidosis and TB are diseases caused by MTB; however, they lie at opposite ends of the same disease spectrum .…”
Section: Introductionmentioning
confidence: 99%
“…Es werden Veränderungen der Interleukin 23/Th17‐Signalwege vermutet, welche gleichzeitig ein mögliches Therapieziel darstellen . Außerdem wird der Effekt verschiedener exogener Faktoren und insbesondere mikrobieller Antigene unter anderem von Myko‐ sowie Propionibakterien diskutiert . Eine kutane Sarkoidose ist die häufigste extrathorakale Manifestation und tritt bei 20–40 % der Sarkoidose‐ Patienten auf.…”
Section: Granulomatöse Dermatosen Bei Systemerkrankungenunclassified